LHP1 Could Act as an Activator and a Repressor of Transcription in Plants - Feng, Jing; Lu, Jiang (Frontiers in Plant Science, 2017)
Polycomb group (PcG) proteins within the polycomb repressive complex 1 (PRC1) and PRC2 are significant epigenetic regulatory factors involved in important cellular and developmental processes in eukaryotes. In Arabidopsis, LIKE HETEROCHROMATIN PROTEIN 1 (LHP1), also known as TERMINAL FLOWER 2, has been proposed as a plant specific subunit of PRC1 that could bind the trimethylated lysine 27 of histone H3 (H3K27me3), which is established by PRC2 and is required for a functional plant PcG system. LHP1 not only interacts with PRC1 to catalyze monoubiquitination at lysine 119 of histone H2A but also functions with PRC2 to establish H3K27me3. This review is about the interaction of LHP1 with PRC1 and PRC2, in which LHP1 may act as a bridge between the two. Meantime, this review highlights that LHP1 could act as an activator and a repressor of transcription.